Activatable endoplasmic reticulum-targeted NIR fluorescent probe with a large Stokes shift for detecting and imaging chymotrypsin. Issue 18 (10th August 2022) - Lan, Ting; Tian, Qin-qin; Li, Ming-hua; He, Wei
Abstract : In this work, the first endoplasmic reticulum-targeted near-infrared fluorescent probe, ISO-Chy, with a large Stokes shift is reported by introducing a recognition group of 4-bromobutyl for chymotrypsin detection. Abstract : In this work, the first endoplasmic reticulum-targeted near-infrared fluorescent probe, ISO-Chy, with a dicyanoisophorone derivative as a fluorophore is reported by introducing the recognition group of 4-bromobutyl for chymotrypsin detection. The probe can be easily synthesized and has shown satisfactory sensitivity and selectivity to chymotrypsin. Meanwhile, ISO-Chy has a large Stokes shift (135 nm) to minimize self-absorption and interference from autofluorescence and then generate significant fluorescence enhancement upon incubation with chymotrypsin. Additionally, ISO-Chy has an excellent ability to target the endoplasmic reticulum, along with preferable Pearson's correlation coefficients ( R r ) of 0.9411 and 0.9522 in P815 cells and HepG2 cells, respectively. Moreover, ISO-Chy was successfully utilized to visualize endogenous chymotrypsin in P815 cells and HepG2 cells and was first used to detect chymotrypsin activity in HepG2 tumor-bearing mice. These findings indicate that ISO-Chy could be an effective tool for detecting endogenous chymotrypsin activity, supporting its use for investigating chymotrypsin function in pathologic processes.